Access to Mudharabah and Musyarakah Financing and MSME Growth: the Mediating Role of Capital Management Effectiveness in Deli Serdang Regency - Sabaruddin Chaniago; Muhammad Fathoni; Cici Handayani; Mhd Restu Razaq; Nurjafa Nurjafa (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Micro, small, and medium enterprise (MSME) growth depends greatly on entrepreneurs’ ability to access appropriate financing and manage capital efficiently. Within the Islamic economic framework, mudharabah and musyarakah financing offer partnership-based funding mechanisms founded on fairness, transparency, and profit-sharing agreements. These instruments are particularly relevant to MSMEs because they provide capital while promoting a more balanced relationship between business owners and Islamic financial institutions.This study aims to examine the effects of access to mudharabah and musyarakah financing on MSME growth, with capital management effectiveness serving as a mediating variable in Deli Serdang Regency. A quantitative associative design will be applied to MSME owners or managers who currently use or have previously used Islamic financing. Respondents will be selected through purposive sampling, while primary data will be collected using structured questionnaires.The proposed analysis will employ Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among the variables. Financing access will be measured through ease of access, suitability of requirements, contract clarity, affordability of profit-sharing arrangements, and institutional support. Capital management effectiveness will cover planning, utilization, control, and evaluation. MSME growth over time will be reflected in sales, profit, assets, customer base, and sustainable operational capacity.